The Potential Role of Bile Acids in Acquired Laryngotracheal Stenosis. (5th February 2018) - Aldhahrani, Adil; Powell, Jason; Ladak, Shameem; Ali, Mahmoud; Ali, Simi; Verdon, Bernard; Pearson, Jeffrey; Ward, Chris
Abstract : Objective: Gastroesophageal reflux is thought to be a risk factor for laryngotracheal stenosis. Bile acids are a component of gastric refluxate and have previously been implicated in the development of fibrosis in other airway subsites. There is clear evidence that bile acids reflux into the upper airway. We therefore investigated the potential role of bile acids in the pathophysiology of laryngotracheal fibrosis and stenosis, specifically investigating the highly conserved process of epithelial–mesenchymal transition (EMT). Study Design: Translational research study. Methods: Human primary tracheal epithelial cells (PTECs) were challenged with the four most common digestive bile acids (cholic, chenodeoxycholic, deoxycholic, and lithocholic). EMT markers transforming growth factor (TGF)‐β1, Matrix metalloproteinase (MMP)‐9, and procollagen proteins were measured in the supernatant at 48 hours via enzyme‐linked immunosorbent assay. Real‐time polymerase chain reaction was also used to measure E‐cadherin and fibronectin expression. Results: Significantly greater concentrations of TGF‐β1 and MMP‐9 were measured in the culture supernatants of cells treated with each bile acid at 10 µmol/L. Lithocholic acid and deoxycholic acid induced significantly increased expression of procollagen protein. Upregulation of fibronectin and downregulation of E‐cadherin were observed with all bile acids, except for deoxycholic acid. Conclusion: This is the first proof of principle demonstration that physiologically relevant bile acid challenge induces EMT mechanisms in PTECs. This implies a potential role for bile acids in laryngotracheal scarring and airway remodeling of potential translational significance in laryngotracheal stenosis. Level of Evidence: NA. Laryngoscope, 128:2029–2033, 2018